2022
DOI: 10.3390/pathogens11080916
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Household Disinfection Techniques to Remove SARS-CoV-2 from Cloth Masks

Abstract: To assess the efficacy of washing cloth masks, we simulated SARS-CoV-2 contamination in tricoline fabric and tested decontaminants to reduce viral particles. Viral suspensions using two variants (B.1.1.28 and P.1) were inoculated in these fabrics, and the inactivation kinetics were evaluated after washing with various household disinfection products (Soap powder, Lysoform®, Hypochlorite sodium and 70% Alcohol), rinse numbers, and exposure times. Afterward, the fabrics were washed in sterile water, and viral RN… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…The study showed that all biocidal treatments successfully disinfected the tissue tested. This work was published in Pathogens in 2022, under the [90].…”
Section: Discussionmentioning
confidence: 99%
“…The study showed that all biocidal treatments successfully disinfected the tissue tested. This work was published in Pathogens in 2022, under the [90].…”
Section: Discussionmentioning
confidence: 99%
“…Samples presenting a CT > 35 were considered negative. This standard curve was obtained by purification, quantification, and serial-dilution of SARS-CoV-2 from cell culture [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…This standard curve was obtained by puri cation, quanti cation and serialdilution of SARS-CoV-2 from cell culture. [19]…”
Section: Sars-cov-2 Detection and Quanti Cationmentioning
confidence: 99%
“…Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) is the etiological agent of Coronavirus disease 2019 (COVID- 19) and can be responsible for a wide range of different outcomes, varying from asymptomatic infection, mild disease and even severe acute respiratory syndrome (SARS) and death. [1,2] Although the end of the Public Health Emergency of International Concern for COVID-19 was decreed by the World Health Organization (WHO), on May 5th, 2023, [3] it brought us all relevant questioning, mainly regarding the patients' management and monitoring.…”
Section: Introductionmentioning
confidence: 99%